Accessibility of Sports Facilities and Its Impact on Skill Development Among Junior and Senior High School Student-Athletes - Ians Aprilo; Poppy Elisano Arfanda; M. Adam Mappaompo (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
In rapidly developing urban areas like Makassar City, the commercialization of public spaces often limits school-aged athletes' access to standardized training infrastructure, presenting a structural barrier frequently overlooked in sports pedagogy. This study analyzes the relationship between sports facility accessibility and the skill development of junior and senior high school student-athletes in Makassar. Employing a quantitative correlational design with a cross-sectional approach, the study involved a purposive sample of 30 student-athletes aged 12–15 years with a maximum of two years of training experience. Facility accessibility was measured via a comprehensive questionnaire, while motor skills were assessed through a standardized basic sports skills test, controlling for training frequency and motivation. Data were analyzed using Pearson and partial correlation tests. The results revealed a positive, significant, and moderate relationship between sports facility accessibility and student-athlete skills (r = 0.465; p = 0.001). Training frequency (r = 0.435; p = 0.002) and motivation (r = 0.413; p = 0.002) also significantly correlated with skills. Crucially, partial correlation confirmed that the facility accessibility-skill relationship remained independently significant even after controlling for both frequency and motivation (r = 0.405; p = 0.003). This study proves that the physical environment acts as an independent determinant of motor performance within urban sports pedagogy and sociology. Practically, it provides an empirical foundation for policymakers to design school-centered, highly accessible sports infrastructures to secure sustainable youth athlete development.